The resolution of failed banks during the crisis: Acquirer performance and FDIC guarantees, 2008–2013 - Cowan, Arnold R.; Salotti, Valentina (Journal of Banking & Finance, 2015)
We find that winning bidders in FDIC failed bank auctions from 2008 to 2013 experience substantial positive abnormal stock returns. Returns are inversely related to bid amounts after controlling for bid determinants, consistent with wealth transfers from the FDIC providing implicit subsidies to acquirers. The results challenge arguments that wealth transfers in earlier crises stemmed from since-eliminated bidding restrictions, but support the prediction of cash-in-the-market pricing theory that during crises, resolution through acquisition requires subsidization. Winning bid amounts are related to proxies for cash-in-the-market pricing. FDIC loss sharing, not widely used before the recent failure wave, is an important influence on bids.